A Comparison of the Effects of Two Prey Enrichment Media on Growth and Survival of Pacific Bluefin Tuna, Thunnus orientalis, Larvae. Issue 1 (15th November 2017) - Stein, Maria S.; Margulies, Daniel; Wexler, Jeanne B.; Scholey, Vernon P.; Ryo, Katagiri; Honryo, Tomoki; Sasaki, Tsukasa; Guillen, Angel; Agawa, Yasuo; Sawada, Yoshifumi
Abstract : Three experiments were conducted to investigate the growth, survival, and standardized cohort biomass of Pacific bluefin tuna, Thunnus orientalis, larvae fed nutritionally enhanced prey during the first week of feeding using two commonly used, commercially available enrichment media, AlgaMac Enrich and Marine Glos. T. orientalis larvae exhibited exponential growth in standard length and dry weight. The daily specific growth rates in length and weight are the first reported for T. orientalis larvae and the averages ranged from 3.8 to 4.1% and 27.5%, respectively, for larvae in the AlgaMac treatment and from 4.1 to 6.1% and 31.5%, respectively, in the Marine Glos treatment. Average daily growth rates in length ranged from 0.16 to 0.23 mm/d for larvae in the AlgaMac treatment and from 0.17 to 0.27 mm/d for those in the Marine Glos treatment. Daily growth rates in length were similar to those reported for other tuna larvae reared in the laboratory but slower than most published estimates for larval tunas in situ at similar water temperatures. Mean prey number per gut was positively associated with mean prey level in the tank. Both enrichment media appear to be good sources of nutritional improvement of planktonic prey for T. orientalis larvae.